Toward a Theory of Transnuancing: A Product-Oriented Analysis of Indonesian and Javanese Senandung of Short Qur’anic Verses - Purnomo, SF Luthfie Arguby; Purnama, SF Lukfianka Sanjaya; Umam, Robith Khoiril; Rizal, Muhammad; Sartika, Yustin; Nurisma, Maulidiya Aulia (Jurnal Arbitrer, 2025)
In Indonesia, to strengthen the memorization and comprehension of holy Qur’anic verses among youth, short verses are often adapted into senandung (chanting). This phenomenon is of academic urgency to study as it involves issues of preserving the accuracy and sacredness of the transadapted verses while simultaneously lyricizing them into songs. We argue that this specific transadaptation deserves a new term as a point of departure. We called it transnuancing, a portmanteau of translation and nuancing. To support the claim, we formulated the research questions: 1) what is transnuancing? 2) what are the characteristics of transnuancing? To address the questions, we employed the theories of transadaptation by Purnomo et al. (2022), musical nuance by Roholt (2014), sonic theology by Beck (2021), Maclean, Bryant, and Bradley (1987), and paraphrasing by Gorleé (2005) with analysis techniques by Spradley (2016) in a qualitative design context. Theoretical triangulation was implemented to ensure the data’s validity. The findings indicate that to preserve the accuracy and sacredness of the transadapted verses in Javanese and Indonesian, the translators pay close attention to the nuances of the translation. We classified the nuancing into semantic, aesthetic, and contextual nuancing. Through semantic nuancing, the translation is taken from official translations of the Qur’an. Through aesthetic nuancing, background music or a genre considered solemn was selected to accompany the translation. Through contextual nuancing, the context surrounding the translation was considered. Future studies could investigate the parameterization of the nuancing to determine their numerical weights by involving audience receptions. Through this parameterization process, assessment rubrics that include nuancing as one of the elements could be designed.